Identification, characterization and expression analysis of SHORT INTERNODES (SHI) gene in Jatropha curcas L - Sillapaprayoon, Siwapech; Samipak, Sompid (Agriculture and Natural Resources, 2017)
Physic nut (Jatropha curcas) is a valuable crop whose seeds contain a high percentage of oil and can be converted to high-quality biodiesel. Physic nut can grow in tropical and subtropical areas and has minimal requirements of its environment. Physic nut starts its production 9 mth after planting and its yield peaks in 2-3 yr. The major hurdle in harvesting its seeds is the extreme height of this crop. J. curcas plants often reach 1.5-2 m after the first year and continue to grow. Plant height control had been achieved by manipulating levels of gibberellic acid (GA). One possible way to accomplish GA manipulation is through the action of the SHORT INTERNODES (SHI) gene since it has been found to repress GA responses. The current study identified the SHI gene in J. curcas. Further characterization of the expression pattern and structure of the SHI gene revealed that JcSHI is a single copy gene that encodes 315 amino acid residues and is highly expressed in the shoot meristem and root. The phylogenetic tree showed a close relationship between JcSHI and PtSHI that are both in woody plants. The JcSHI protein contained a specific RING zinc finger (C3HC3H type) and the IGGH domain indicating the possible function of SHI as a transcriptional regulator of genes involved in plant growth and elongation.